Factors influencing student citizenship behavior (SCB) and long–term student relationship orientation (LRO) in Vietnamese education sector - Chau Ngoc Bao Dang; Duc Thai Nguyen; Tung Thanh Le; Vu Hoang Nguyen; Luan Thanh Nguyen (The second international conference on science, economics and society studies – UEF 2023, 2023)
Student citizenship behavior (SCB) is regarded as one of the most significant variables influencing student orientation and the development of long-term relationships between students and higher educational institutions (LRO). The literature confirms that the issue of SCB in the higher education sector is a challenge that must be addressed. Hence, this study aims to examine the antecedents and outcome of SCB by applying linear and non-linear relationships based on the partial least squares structural equation modeling approach (PLS-SEM) and the artificial neural network model (ANN) through building constructs on the stimulus-organization-response framework (SOR). In addition, data was gathered from 185 students from Ho Chi Minh City's universities and colleges. The study's findings indicate that students' stimuli, such as student satisfaction, trust, and loyalty, have a favorable impact on the expression of their citizenship behaviors, such as advocacy, offering feedback, and helping others. In addition, helping others through SCB has a beneficial influence on LRO for higher educational institutions. Finally, through the ANN model, student trust is the most prominent driver of feedback and advocacy. The results of this research provide important insight into the factors that shape the focus and growth of organizations in Vietnam's education sector through long-term collaborations. In addition, this research sheds new light on the impact that students' actions have on SCB, allowing for the development of concrete recommendations for school administrators concerned with fostering the formation of lasting relationships among their students.
Keywords: 330; long-term student relationship orientation; Vietnam higher-education; student citizenship behavior; SEM-ANN approach